2022
DOI: 10.1016/j.ajem.2022.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Bioterrorism: An analysis of biological agents used in terrorist events

Abstract: Background The Covid19 pandemic has reignited debates and discussions around healthcare systems' biosecurity vulnerabilities and cast a spotlight on the potential weaponization of biological agents. Terrorist and violent extremist groups have already attempted to incite the intentional spread of Covid19 and to use it as an improvised form of a biological weapon. This study aims to provide an epidemiological description of all terrorism-related attacks using biological agents sustained between 1970… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…This study follows the methodology suggested by Tin et al in their analysis of biological agents used in terrorist events. 3 The research leverages the open source, retrospective database, the Global Terrorism Database, created by the National Consortium for the Study of Terrorism and Responses to Terrorism. 4 The online, public database includes information on domestic and international terrorist attacks from 1970 to 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study follows the methodology suggested by Tin et al in their analysis of biological agents used in terrorist events. 3 The research leverages the open source, retrospective database, the Global Terrorism Database, created by the National Consortium for the Study of Terrorism and Responses to Terrorism. 4 The online, public database includes information on domestic and international terrorist attacks from 1970 to 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The system excludes any ambiguous events which occur after 1997 and provide some uncertainty as to whether they meet database criteria for inclusion. 4 Additionally, the database does not include state acts of terrorism and defines terrorist attacks as ‘the threatened or actual use of illegal force and violence by a non-state actor to attain a political, economic, religious, or social goal through fear, coercion, or intimidation.’ 3 …”
Section: Methodsmentioning
confidence: 99%
“…26 With advances in biotechnologies and the commercialization of home Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) kits, the plausibility of homemade bioweapons is becoming more likely. 5 In addition, with drones and other technologies such as nanorobots and biologically modified insect vectors, the dispersion of biological agents becomes more possible, potentially deadlier, and "limitless." 27 The combination of genomic technologies with AI, machine learning, automation, affective computing, and robotics will potentially increase the lethality of "old world biologicals" while creating newer and more deadly agents.…”
Section: Biological Agentsmentioning
confidence: 99%
“…1,2 Deadly chemicals are readily available in the industrial sector and home-made bioweapons are increasingly plausible as biotechnologies advance. [3][4][5] In addition, the threat of artificial intelligence (AI) looms as a tool to create innovative chemical weapons that might not otherwise have been conceived of. 6 Further, radiation sources used commonly in the medical sector are vulnerable to theft and modifications and then used to create dirty bombs, and nuclear plants are vulnerable to both cyber hacks and physical damage, which could lead to meltdowns and wide-spread human, structural, and environmental devastation.…”
Section: Introductionmentioning
confidence: 99%
“…It encompasses physical injuries, burns, as well as exposure to chemical, biological, or radiological/nuclear (CBRN) warfare agents. While bioterrorism and B-warfare—so far known—predominantly involve agents such as viruses, bacteria, and bacterial toxins (Botulinum Neurotoxin (Kreyden et al 2000 ), Anthrax toxin) as well as plant toxins (Ricin) (Tin et al 2022 ), the arsenal of chemical warfare agents is extensive (Wille et al 2011 ) and comprises toxic substances that affect the skin, the lungs, or the nervous system. The latter comprises organophosphates such as tabun, sarin, VX, and the Novichok compounds, which can cause a severe, life-threatening cholinergic syndrome, as described in more detail later.…”
Section: Introductionmentioning
confidence: 99%